Cognitive Failure as a Consequence of Video Games, Developing Risk of Disruptive Behaviors among Students - Abdul Sattar Ghaffari; Khizra Iqbal; Shagufta Bibi; Arslan Khalid (Corresponding Author); Basit Nadeem (Al-Qanṭara, 2024)
The recent study aims to explain the excessive level of aggression and cognitive failure among video game player students. Participants were 200 gamers, and 198 were non-gamers in which (149 males and 49 females, only gamers) from Islamia University of Bahawalpur. Two questionnaires were used to measure variables: the Buss-Perry Aggression Questionnaire and the Cognitive Failures Questionnaire. A descriptive research design is used for the study. Data was collected from the co-relation sampling method, and it is analyzed by using the new SPSS version 21. Statistical techniques such as correlation, t-test, mean, and standard deviation were used. The results are very confirmed from the collected data; the greater value of aggression among the gamers is more aggressive than the non-gamers. Gamers have more cognitive failure problems than non-gamers. The study provides the probable negative impacts and consequences of violent video games on students. The present study found that students who play video games excessively have more aggression and cognitive problems than students who avoid playing video games. The results of studies indicated that the students who do not play video games have less physical aggression, verbal aggression, anger, hostility, and cognitive failure problems. The present study found that students who play video games excessively have more aggression and cognitive problems than students who avoid playing video games. The results of studies indicated that the students who do not play video games have less physical aggression, verbal aggression, anger, hostility, and cognitive failure problems.